Thermal control of a light-weight rover system in the permanently shadowed regions of the lunar south pole - Ivanov, Dmitri; Fernandes, Domingos (2020 International Conference on Environmental Systems, 2020)
Dmitri Ivanov, ispace Europe, LU Domingos Fernandes, ispace Europe, LU ICES102: Thermal Control for Planetary and Small Body Surface Missions The proceedings for the 2020 International Conference on Environmental Systems were published from July 31, 2020. The technical papers were not presented in person due to the inability to hold the event as scheduled in Lisbon, Portugal because of the COVID-19 global pandemic. The exploration of the Earth’s Moon has become a topic of great interest in recent years to both private and governmental entities. ispace is aiming to be the enabler for private industry to access new business opportunities on the Moon by capitalizing on lunar resources and expanding our presence in space. The Polar Ice Explorer (PIE) is an in-situ resource utilization (ISRU) exploration mission that aims to find and characterise potential water ice deposits in the lunar polar regions. In the scope of this project, the rover thermal control system development will be discussed. PIE leverages on ispace developed and flight qualified Team HAKUTO’s SORATO rover. The paper explores findings from three key areas: operations in the permanently shadowed regions (PSR) of lunar poles, thermal control design of the rover system and modelling of lunar environment. Thermal modelling of the lunar polar region was conducted with a particular attention towards identification of surface properties, lunar regolith characteristics and modelling of environmental fluxes. Operational mission constraints, such as cooling rates and heater power requirements, were investigated. Thermal design philosophy aimed to maximise passive control means through decoupling of the rover from the ground, reduction of heat losses and conductive path management. Mechanical issues induced by larger temperature swings were investigated. Active control means were considered for elements with tighter operational ranges, such as batteries, motors and externally mounted elements. The rover thermal design challenges and preliminary ...